Reprsentasi Perempuan dalam Gadis Pantai Karya Prmoedya Ananta Toer - Ridwan, Ridwan; Abidin, Aslan; Puspa Darwini, Nurul Fadhilah (University of Brawijaya, 2025)
This research aims to find out how the image of women is reconstructed in the novel Gadis Pantai by Pramoedya Ananta Toer. The research method used in this analysis is descriptive qualitative, focusing on understanding social phenomena in the novel using a feminist literary approach. Data collection techniques are carried out by reading repeatedly and noting important points of the data found to avoid errors in collecting data information. The data collected is then analyzed by linking the representation of women using feminist criticism studies. The results of the analysis show that Gadis Pantai's position as a Javanese woman faces various challenges and gender violence that shows social injustice in society at that time. The novel reveals in depth how gender and violence against women are understood in traditional Javanese society, and emphasizes the urgency of gender equality and the protection of women's rights in the modern era. Women are often marginalized in Javanese life, especially in daily tasks and in the social hierarchy. In addition, the novel also depicts violence against women, both physical and psychological.